2019
DOI: 10.3390/su11123309
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Rural Tourism as an Economic Diversification and Regional Development Instrument. The Case Study of the Region of La Vera

Abstract: In the mid-1980s, at the same time as the Common Agricultural Policy (CAP) reforms resulted in a decrease in agricultural employment, the Single European Act transformed the reduction of regional differences into an objective of European regional policy. The LEADER Initiative and the PRODER Program were two of the instruments chosen by the European Commission to deal with the effects that these new challenges would have for the rural environment. This research studies the scope and limitations of these program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…Only the motivations that depend on internal conditions of the visitor, such as the search for rest and the preference for local produce, have a significant influence on the decision to stay overnight and increasing LOS. A number of previous studies have identified limited tourist products as one of the weaknesses facing rural tourism [17,19,21]. Local stakeholders should expand the range and availability of activities for visitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the motivations that depend on internal conditions of the visitor, such as the search for rest and the preference for local produce, have a significant influence on the decision to stay overnight and increasing LOS. A number of previous studies have identified limited tourist products as one of the weaknesses facing rural tourism [17,19,21]. Local stakeholders should expand the range and availability of activities for visitors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have drawn attention to the limitations of tourism as an instrument for diversification and regional development [17]. Others have qualified the dimension of its impacts, which may be limited by questions such as infrastructures, accessibility, a lack of attractions, the sizes of establishments, the greater weight of domestic demand, or the low number of activities carried out by tourists in rural areas [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It widely recognized that programmes such as LEADER are flagship initiatives for the EU sustainable rural-local development and sustainable rural tourism [32] as entrepreneurial ideas and efforts in rural tourism are recourseless and financial support such as EU rural development programmes can contribute in enhancing entrepreneurial activities in the rural tourism sphere [33]. To this extent, the EU development programmes offered the opportunity for the expansion of rural tourism [34] and the income of rural habitants increased as agriculture production started to decline [29]. The EU is suffering from agricultural land abandonment [35] and sustaining rural areas through alternatives ways is vital for the EU rural areas and the EU agricultural production.…”
Section: Literature Review: Rural Tourism and Challenges In The Eu Dementioning
confidence: 99%
“…However, this is not the only novelty included in this study. Although there are many methodologies used in the analysis of Leader aid, surveys [17,43], spatial location analysis [22], multicriteria analysis [45], efficiency analysis [40], etc., the use of cluster analysis employed in this article is non-existent in this field and represents an advance in the scientific contribution by relating the survival of the investments with the spatial location of these projects, their relationship with other context variables and locating clusters of territories where optimal conditions have been produced for the maintenance of these projects over time. In addition, they can serve as a model for a better design of this type of public investment in other rural areas or to analyze the survival of other types of Leader investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In response to this situation and in order to reduce the differences with urban areas [15], the EU designed rural development initiatives based on three key aspects: to equalize the standard of living of urban and rural areas, to promote the establishment of diversified productive activities, strengthening the industrial and service sectors, and to halt the depopulation and decline of rural areas [16], at a time when changes in the Common Agricultural Policy were causing a reduction in agricultural employment [17] and lower incomes in rural economies [18].…”
Section: Introductionmentioning
confidence: 99%